2021
DOI: 10.3897/folmed.63.e52343
|View full text |Cite
|
Sign up to set email alerts
|

Communication Skills Teaching Methods in Dental Education – a Review

Abstract: Communication skills of dentists have been demonstrated to be part of the good dental practice. The aim we set ourselves in this study was to review the literature related to the methods of teaching communication skills at dental faculties, and develop a handout in the Bulgarian language about leading a successful conversation with a patient. According to some authors, the most important principles for effective communication training include the use of practical exercises, clinically relevant scenar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…• Role of clinical instructors Burkert, 2021 ■ Narrative review reported that ultimate learning of optimal communication skills requires teachers to be role models, effective supervisors, powerful tutors, and supportive persons who use diverse teaching methods with an individual approach to educating their students.…”
Section: Carey Et Al 2010mentioning
confidence: 99%
See 4 more Smart Citations
“…• Role of clinical instructors Burkert, 2021 ■ Narrative review reported that ultimate learning of optimal communication skills requires teachers to be role models, effective supervisors, powerful tutors, and supportive persons who use diverse teaching methods with an individual approach to educating their students.…”
Section: Carey Et Al 2010mentioning
confidence: 99%
“…Burkert's review [33] reported that the ultimate learning of optimal clinical communication skills requires teachers to be "good role models, effective supervisors, powerful tutors and supportive persons who use dynamic and diverse teaching methods and have an individual approach to educating their students." Ayn et al [15] also underscored the role of the clinical instructor in modeling clinical communication skills as a form of learning in which there is very little educational institution control over its quality.…”
Section: The Role Of Clinical Instructors In Communication Skills Lea...mentioning
confidence: 99%
See 3 more Smart Citations